Effects of xenoestrogens in human M1 and M2 macrophage migration, cytokine release, and estrogen-related signaling pathways - Teixeira, D (2015)
Bisphenol A (BPA), bis(2-ethylhexyl)phthalate (DEHP) and di(n-butyl)phthalate (DBP) are environmental estrogens that have been associated with a wide range of adverse health outcomes for which inflammation has also been hypothesized as a potentially involved mechanism and where macrophages play a central role. This study was carried out to evaluate if xenoestrogen (XE) treatment of classically (M1) or alternatively (M2) activated macrophages could affect their behavior. For this purpose, human peripheral blood monocyte-derived macrophages either unstimulated or activated with lipopolysaccharide (100 ng/mL, M1) or with interleukin (IL) 4 (15 ng/mL, M2) were treated with 17ß-estradiol (E2), BPA, DEHP and DBP alone or in combination with selective ER or ERß antagonists. Migratory capability, cytokine release, and estrogen-associated signaling pathways were evaluated to assess macrophage function. All tested XEs had a tendency to stimulate M2 migration, an effect that followed the same direction than E2. Moreover, all XEs significantly induced IL10 in M1 and decreased IL6 and globally decreased IL10, IL6, TNF, and IL1ß release by M2 macrophages. However, DEHP and DBP significantly increased IL1ß release in M1 and M2 macrophages, respectively. Some of the effects described above were shown to be mediated by either ER or ERß and were simultaneous to modulation of NF-B, AP1, JNK, or ERK signaling pathways. We provide new evidence of the effect of XE on macrophage behavior and their mechanisms with relevance to the understanding of the action of environmental chemicals on the immune system and inflammation-associated diseases. © 2015 Wiley Periodicals, Inc.